Organizational Culture and Customer Loyalty: A Case of Harvey Norman - Lim, Yii Han; Kee, Daisy Mui Hung; Lai, Xiao Yu; Lee, Ze Minn; Low, Mei Qi; Sariya, Sariya; Sharma, Sakshi (AIBPM Publisher, 2020)
Harvey Norman is an Australian company that offers broad product range for their customers. Customers are key element of success for a business. When customers get the satisfaction, they expect from the brand, it will result in customer loyalty indirectly. Therefore, our group decided to conduct a research on determining the key driver of having customer loyalty and satisfaction towards our company brand. Besides that, we would like to determine the relationship between customer loyalty and customer satisfaction. We aim to identify how would the variables be affected by the management culture of the company. The research methods used in this study include quantitative method and qualitative method.